SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN - Muhammad Hasan Basari; Muhammad Irsyad Fahlevi; Supriyadi; Trias Pangestu Aji Sanjaya (CV. Adiba Aisha Amira, 2026)
Educational supervision is an essential component of educational management that plays a strategic role in improving the quality of learning in schools. Supervision does not merely function as a control mechanism but also serves as a continuous professional development effort aimed at enhancing teachers’ competencies. This article seeks to analyze the concept of educational supervision, including its definition, objectives, functions, principles, models, techniques, as well as the challenges and solutions in its implementation. The research method employed is a literature review by examining relevant books, regulations, and scientific journal articles. The findings indicate that educational supervision conducted in a professional, democratic, and collaborative manner can significantly improve teachers’ pedagogical competence and contribute to the enhancement of learning quality in educational institutions.